Visually representative web history browser : a thesis submitted to the College of Creative Arts, Massey University, New Zealand, as fulfilment for the degree Master of Design - Hodgkinson, Gray (Massey University, 2007)
The familiar computer graphic user interface (GUI) makes extensive use of visually representative devices such as folders and files. These symbols help the user deal with computer data and operations that otherwise have little or no physical form. The computer’s underlying complexity is symbolised for the user, who is then able to manipulate the computer by interacting directly with the interface. The early development of computer interface design was largely the domain of software and hardware developers. Many sound principles of user interaction and testing were established and provided essential guidance for new generations of interface designers. As computer technology and its tools became more widely available, a broader range of designers began contributing, including those from product design and visual communication. This study is written from the point of view of a “visual designer” – a designer who began his career in graphic design and who has moved towards interface design out of curiosity and a desire to proffer a different attitude and approach to interface issues. The study therefore will demonstrate a design process that many visual designers will be able to identify with. The process includes research, analysis, methodical progression and artistic inspiration. The artistic inspiration in this case comes from the Constructivist artist El Lissitzky, and will illustrate the significant contribution that art can make to interface design. This art-influenced design process was presented at the 2005 Ed-Media World Conference on Educational Multimedia, (Montreal, 2005). The enthusiastic response and discussion provided encouragement to continue in this direction. In the following year another presentation, which included the working prototype, was presented as part of a keynote speaker presentation at the 2006 Siggraph Taipei Conference, National Chiao Tung University, Taipei. The specific task chosen to work with in this study is that of Web browser history. As a user browses the Web the computer records a list of visited websites. The first few generations of browsers presented this information as a simple list, but this approach incorporated many flaws and caused problems for users. More recent browsers provide more options, but significant issues remain. This study offers solutions to several of these problems. The resulting design prototype is named “isoBrowser”. It is the result of the alternative design process outlined above and offers alternative methods of visualising, organising and manipulating data. The prototype is not intended to be fully functional nor “live”. However, it is sufficiently operable so as to test interface interaction and user response. A fully functional version, operably and aesthetically complete, would be the subject of further development.
Keywords: World Wide Web; Web browser; Graphical user interface; Web history; Design; Internet; Fields of Research::410000 The Arts::410200 Visual Arts and Crafts Studies